Analisis Tingkat Literasi Digital Orang Tua Pada Pendidikan Anak Usia Dini (PAUD) - Tri Rahayu; Anita Muliawati; Erly Krisnanik; Catur Nugrahaeni Puspita Dewi (Jurnal Ilmiah Matrik, 2022)
The development of digital technology in the current era, especially in the field of education as a means of support for learning in Early Childhood Education (PAUD) students. In the context of education, good digital literacy also plays a role in developing one's knowledge of certain subject matter by encouraging curiosity and creativity. The teaching system for early childhood is not fully borne by educators (teachers) but there is parental involvement. The purpose of this study is to analyze the digital literacy of parents in Early Childhood Education (PAUD) in three indicators, namely accessing, selecting and understanding. The research method used is descriptive by using a qualitative and quantitative approach, where the population of PAUD parents is at Lily Kindergarten in Limo District, Depok. The results of this study are to determine the level of parental digital literacy skills in providing early childhood learning, it is hoped that every parent is able to assist the digital-based early childhood learning system. The results of data processing obtained that the level of parental literacy competence from the survey results was obtained; accessing the value is 84.53% with a high category, for the Selecting dimension the value is 72.00% in the Medium category and the Understanding dimension is 80.00% in the High category.